Programa educativo de comunicación asertiva para mejorar el acompañamiento directivo en las instituciones educativas nivel primaria Nauta 2024 - Tepo Mendoza, Susana Maribel (2025)
The objective of this research was to evaluate the effect of implementing an assertive communication educational program to improve directorial support in primary education institutions in Nauta during 2024. An evaluative research type with a field-based, univariate, and longitudinal design was used. The population included all primary school directors (n = 54), equally divided into a control group (n = 27) and an experimental group (n = 27). A written performance test of case scenarios, used both as a pretest and posttest, was employed, and this test had been previously validated by experts in the field. The results indicate that although both groups showed comparable initial performance levels, the experimental group demonstrated significant improvement after the intervention. The proportions in deficient and regular levels in the experimental group decreased notably, while the excellent level rose from 7.4% to 74.1% in the posttest. These findings suggest that the intervention with the assertive communication educational program had a significant positive effect on the directors' performance, enhancing their skills and competencies and reaching a level of excellence in most cases.